Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/1744-9987.13570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative arterial and venous diameter on achievement of the adequate blood flow in arteriovenous fistula for hemodialysis

Abstract: An arteriovenous fistula (AVF) remains the best choice of vascular access (VA) for hemodialysis (HD). The aim of the study was to determine the factors associated with the achievement of adequate blood flow (BF) of AVFs at the 4th week after creation. Created AVFs in 63 patients with chronic kidney disease (CKD) stage 4/5 and CKD stage 5 on hemodialysis (CKD5D) were analyzed in a prospective study. Doppler ultrasound (DUS) was used for measuring the diameter of the radial artery, the brachial artery and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There is ongoing debate on whether female sex is a risk factor for AVFT. Gjorgjievski et al [41] found that females are more likely to develop AVFT because they have smaller average preoperative arterial diameters and are less likely to achieve adequate BF. After AVF construction for 4 weeks, 12% of the female participants and 63% of their male counterparts achieved adequate BF, defined as 600 mL/min (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing debate on whether female sex is a risk factor for AVFT. Gjorgjievski et al [41] found that females are more likely to develop AVFT because they have smaller average preoperative arterial diameters and are less likely to achieve adequate BF. After AVF construction for 4 weeks, 12% of the female participants and 63% of their male counterparts achieved adequate BF, defined as 600 mL/min (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%